2021
DOI: 10.1136/jitc-2020-002092
|View full text |Cite
|
Sign up to set email alerts
|

Radiological dynamics and SITC-defined resistance types of advanced melanoma during anti-PD-1 monotherapy: an independent single-blind observational study on an international cohort

Abstract: BackgroundAlthough the Society for Immunotherapy of Cancer (SITC) Immunotherapy Resistance Taskforce recently defined primary and secondary resistance to anti-programmed cell death protein 1 (anti-PD-1) therapy, there is lack of real-world data regarding differences in these resistance subtypes with respect to radiological dynamics and clinical manifestations.MethodsWe performed single-blind re-evaluations of radiological images by independent radiologists on a retrospectively assembled cohort of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our previous data showed that major antitumor response was established within 6 months after anti–PD-1 monotherapy initiation ( 12 ), we thus hypothesized the timing of high-dose GCC use in patients who were irAE(+) may affect subsequent outcomes. Noticeably, there was a high degree of variability in terms of onset time of high-dose GCC–associated irAEs ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous data showed that major antitumor response was established within 6 months after anti–PD-1 monotherapy initiation ( 12 ), we thus hypothesized the timing of high-dose GCC use in patients who were irAE(+) may affect subsequent outcomes. Noticeably, there was a high degree of variability in terms of onset time of high-dose GCC–associated irAEs ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, traditional chemotherapy, even with previous immunotherapy exposure, remains associated with dismal outcomes, as previously observed after anti-PD-1 monotherapy failure in the metastatic setting. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…24 Resistance was defined based on minimum drug exposure requirement, best response, and confirmatory scans for primary resistance, secondary resistance, and disease progression after discontinuation of therapy. These definitions have been shown to be associated with distinct clinical outcomes 25 and incorporated into a number of clinical trials' eligibility criteria, supporting their utility for drug development. An ever-increasing number of patients, however, are being treated with ICIs in the context of combination regimens, warranting the revisiting of resistance definitions for ICIs administered in combination with chemotherapy.…”
Section: Introductionmentioning
confidence: 95%